INSCYD physiological performance software is valid to determine the maximal lactate steady state in male and female cyclists - Poffé, Chiel; Van Dael, Kaat; Van Schuylenbergh, Reinout (Frontiers in Sports and Active Living, 2024)
Introduction The maximal lactate steady state (MLSS) is defined as the highest workload that can be maintained without blood lactate accumulation over time. The power output at MLSS (PMLSS) is regularly implemented to define training zones, quantify training progress, or predict race performance. The gold standard methodology for MLSS determination requires two to five trials of constant-load exercise, which limits the practical application in training. The INSCYD software can calculate the PMLSS (PMLSSINSCYD) based on physiological data that can be obtained during a ∼1 h laboratory visit. However, to the best of our knowledge, the validity of the most recent software version has not yet been investigated. This study aimed to assess the validity of the software's calculations on PMLSS in cycling. Methods The data for this study were retrieved from two published scientific sources. Thirty-one cyclists (19 males, 12 females) performed a 15 s sprint to estimate the VLamax, a ramp test for the V˙O2max assessment, and two to five constant-load tests to determine the PMLSS. The INSCYD software was used to calculate the PMLSS based on the V˙O2max, VLamax, sex, body mass, and body composition. Results The PMLSSINSCYD was higher than the PMLSS in the entire sample (mean difference: 4.6 W, p < 0.05, 95% CI 0.8–8.3 W) and in men (mean difference: 6.6 W, p < 0.05, 95% CI 1.3–11.8 W), but not in women (mean difference: 0.8 W, n.s., 95% CI −3.7 to 5.3 W), which was within the typical error of the PMLSS estimations (∼3%). In 12 subjects (nine males, three females), the PMLSSINSCYD differed by 3.1–7.3% compared to the MLSS. The Pearson correlations between the measured PMLSS and the calculated PMLSS (PMLSSINSCYD) were very strong in men (r = 0.974, p < 0.001, 95% CI 0.933–0.99), women (r = 0.984, p < 0.001, 95% CI 0.931–0.996), and for the entire sample (r = 0.992, p < 0.001, 95% CI 0.982–0.996). Discussion In conclusion, the PMLSS can be accurately calculated using the INSCYD software, but it still requires advanced testing equipment to collect valid V˙O2max and VLamax data.